Analysis of Factors Influencing the Managerial Performance of Regional Works Units SKPD) of Banda Aceh City Government - Sari, Dewi Maya; Ikhwal, Muhammad; Soufyan, Dara Angreka (Puslatbang KHAN, 2023)
This study aims to investigate how managerial performance at SKPD Banda Aceh City Goverment is influenced by management control system, public accountability, and clarity of budget targets. The 44 SKPDs in Banda Aceh City, which included organizations, institutions, and offices, made up the study's population. The Head of Service, Head of Finance, Finance Staff, and Secretaries from each SKPD participated in this survey as respondents. There were as many as 176 surveys distributed. There were 152 questionnaires that were returned. A number of linear regressions were used to analyze the data. The study's findings demonstrate that clear budget targets, management control systems, and public accountability all significantly and positively affect managerial performance at SKPD Kota Banda Aceh.